Social unrest and popular protest in England, 1780-1840 / John E. Archer. - Archer, John E. (New studies in economic and social history ;, 2000)
This text examines the diversity of protest from 1780 to 1840 and how it altered during this period. It covers all forms of protest, including the Gordon Riots of 1780, food riots, and Luddism, up to the advent of Chartism in the 1830s